2019
DOI: 10.1186/s13054-019-2704-2
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic use of levosimendan in pediatric patients undergoing cardiac surgery: a prospective randomized controlled trial

Abstract: BackgroundThe administration of levosimendan prophylactically to patients undergoing cardiac surgery remains a controversial practice, and few studies have specifically assessed the value of this approach in pediatric patients. This study therefore sought to explore the safety and efficacy of prophylactic levosimendan administration to pediatric patients as a means of preventing low cardiac output syndrome (LCOS) based upon hemodynamic, biomarker, and pharmacokinetic readouts.MethodsThis was a single-center, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 37 publications
0
40
0
1
Order By: Relevance
“…Thirty-six literatures were excluded because they did not meet the eligible criteria by browsing the titles and abstracts, and 16 literatures were removed by browsing the full text. Eventually, 7 trials including 436 patients were indentified through our search strategy [ Figure 1 ; ( 24 30 )].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-six literatures were excluded because they did not meet the eligible criteria by browsing the titles and abstracts, and 16 literatures were removed by browsing the full text. Eventually, 7 trials including 436 patients were indentified through our search strategy [ Figure 1 ; ( 24 30 )].…”
Section: Resultsmentioning
confidence: 99%
“…The basic information of all included trials is shown in Table 1 . Four trials ( 24 , 26 28 ) were conducted in European countries, and 3 trials ( 25 , 29 , 30 ) in Asian countries. All patients included in the 7 articles were under 5 years old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study by Wang et al on levosimendan used in prophylaxis of low cardiac output syndrome (LCOS) post-pediatric cardiac surgery is the first study comparing levosimendan versus placebo. The authors did not show an impact on mortality or on the occurrence of LCOS [1]. However, it is very interesting to see that in the multivariate regression analysis, levosimendan had an impact on the onset of LCOS (OR 0.38 and p = 0.037).…”
mentioning
confidence: 87%